Amazon expeditions : my quest for the ice-age equator - Colinvaux, Paul, 1930- (Yale University Press, 2007)
"In this memoir of a life in science, ecologist Paul Colinvaux takes his readers from the Alaskan tundra to steamy Amazon jungles, from the Galapagos Islands (before tourists had arrived) to the high Andes and the Darien Gap in Panama. He recounts an adventurous tale of exploration in the days before GPS and satellite mapping, and a tale no less exhilarating of his battle to disprove a hypothesis endorsed by most of the scientific community."--Jacket